Prevalência das famílias TEM, SHV e CTX-M de β-lactamases de espectro entendido em Escherichia coli e Klebsiella spp. no Hospital Universitário de Santa Maria, Rio Grande do Sul - Oliveira, Caio Fernando de (2009)
Extended-spectrum β-lactamases (ESBLs) are plasmid-mediated bacterial enzymes that confer resistance for most β-lactams antibiotics. These enzymes are widespread in microorganisms in hospital settings worldwide. This study estimated the distribution and prevalence of the main ESBLs families among samples of Escherichia coli and Klebsiella spp. in the university hospital of Santa Maria (HUSM), Rio Grande do Sul. During a period of 14 months 90 microorganisms were selected as probable ESBL producers according to the recommendations of Clinical and Laboratory Standards Institute (CLSI). The isolated microorganisms were submitted to phenotypic confirmatory tests for the presence of ESBL. Samples that showed negative results were tested against their susceptibility to cefoxitin. The ESBLs types found in each organism were determined by the research of the genes bla TEM, bla SHV e bla CTX-M by polymerase chain reaction (PCR). Fifty-five (61.1%) samples were confirmed as ESBL positive by the combined disc method and fifty-seven (63.3%) by the double disc method. In the cefoxitin susceptibility test 16 of the 39 samples presented resistance to this agent. Based on PCR, 74 (82,2%) samples harbored TEM-type ESBL gens, 61 (67,8%) SHV-type and 19 (21,1%) CTX-M-type. Only one Escherichia coli isolate appeared harboring genes for the CTX-M family of ESBLs. The distribution of TEM, SHV and CTX-M ESBL families from HUSM presented some similarities and differences compared with ESBLs of other hospital settings.